Social Relations of Multiethnic Communities in Banjarmasin City (A Study of the Kampung Gadang Community) - M. Ridha Ilhami; Muhammad Rezky Noor Handy; Syaharuddin Syaharuddin; Raihanah Sari; Sovia Husni Rahmia; Hijjatul Alawiyah; Muhammad Aufar Athala (The Kalimantan Social Studies Journal, 2025)
This article examines the social relations within the multiethnic community in Kampung Gadang, Banjarmasin City, which is renowned as one of the most tolerant cities in Indonesia. The study focuses on the dynamics of interactions between the Banjar, Javanese, Madurese, and Chinese ethnic groups. Using qualitative descriptive methods, the research, conducted from July to August 2025, analyzed how the community in Kampung Gadang maintains social harmony amidst diversity. The results indicate that social relations can be categorized into two forms: associative and dissociative. The associative form is manifested through strong cooperation (gotong royong), where residents from various ethnic backgrounds help each other during celebrations and community service. Accommodation occurs when these ethnicities respect each other's traditions and customs. Furthermore, assimilation is evident in the ability of newcomers to adapt to local culture and speak the Banjar language. Dissociative relations are well managed through rapid deliberation. Local wisdom, such as the value of "Bahari" (patience) and the principle of "Mufakat" (negotiating together), serves as a strong foundation for maintaining harmony. This study concludes that solid social interactions, grounded in local wisdom, enable multiethnic communities to live harmoniously and harness diversity as a collective strength.